Towards polymerase-mediated synthesis of artificial RNA–DNA metal base pairs. (21st February 2022) - Levi-Acobas, Fabienne; McKenzie, Luke K.; Hollenstein, Marcel
Abstract : Polymerase-mediated synthesis of RNA-DNA metal base pairs. Abstract : Metal-mediated base pairs are formed by the connection of two nucleobases via coordination to a metal cation. The resulting metal-containing duplexes have been used in a large variety of applications ranging from allosteric control of functional nucleic acids to the construction of nanowires. Recently, enzymatic approaches are being developed for the construction of metal-mediated base pairs. Here, we have studied the possibility of constructing Hg II - and Ag I -mediated DNA/RNA hetero base pairs using primer extension reactions. The high thermodynamic stabilities of metal base pairs can be harnessed to trigger the formation of two rU–Hg II –dT base pairs. Bypass experiments demonstrate the possibility of constructing RNA containing DNA sequences which are used in multiple applications including DNAzyme selections. These findings will be useful for the enzymatic construction of xenonucleic acid (XNA) based metal pairs.